Venom Atypical Extracellular Vesicles as Interspecies Vehicles of Virulence Factors Involved in Host Specificity: The Case of a Drosophila Parasitoid Wasp - Wan, Bin; Goguet, Emilie; Ravallec, Marc; Pierre, Olivier; Lemauf, Séverine; Volkoff, Anne-Nathalie; Gatti, Jean-Luc; Poirié, Marylène (Frontiers in Immunology, 2019)
Endoparasitoid wasps which lay eggs inside the bodies of other insects use various strategies to protect their offspring from the host immune response. The hymenopteran species of the genus Leptopilina, parasites of Drosophila, rely on injection of a venom which contains proteins and peculiar vesicles (hereafter venosomes). We show here that the injection of purified L. boulardi venosomes is sufficient to impair the function of the Drosophila melanogaster lamellocytes, a hemocyte type specialized in the defense against wasp eggs, and thus the parasitic success of the wasp. These venosomes seems to have a unique extracellular biogenesis in the wasp venom apparatus where they acquire specific secreted proteins/virulence factors, and act as a transport system to deliver these compounds into host lamellocytes. The level of venosomes entry into lamellocytes of different Drosophila species was correlated with the rate of parasitism success of the wasp, suggesting that this venosome-cell interaction may represent a new evolutionary level of host-parasitoid specificity.